Space Exploration 2008 - Harland, David M. (Springer, 2017)
The aim of the Space Exploration annuals is to provide a yearly update on recent space launches, missions and results, to be published every September. The annual will cover space exploration from a variety of angles, looking back at past missions, reviewing those currently under way and detailing those planned for the future, and encompassing both manned and unmanned spaceflight.